The Role of ARF Family Proteins and Their Regulators and Effectors in Cancer Progression - Casalou, Cristina (2020)
AF was funded by a Ph.D. fellowship (PD/BD/135506/2018) from the Fundação para a Ciência e a Tecnologia (FCT) and DB by the FCT Investigator Program (IF/00501/2014/CP1252/CT0001).